CCDA III Exhibition - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Photos from the Third Conference on Climate Change and Development in Africa - CCDA III - Exhibition. CCAFS East Africa shared with over 300 partcipants some of our latest research outputs.